Identification of B-Cell Epitope of Dengue Virus Type 1 and Its Application in Diagnosis of Patients - Wu, Han-Chung (American Society for Microbiology, 2001)
Using a serotype-specific monoclonal antibody (MAb) of dengue virus type 1 (DEN-1), 15F3-1, we identified the B-cell epitope of DEN-1 from a random peptide library displayed on phage. Fourteen immunopositive phage clones that bound specifically to MAb 15F3-1 were selected. These phage-borne peptides had a consensus motif of HxYaWb (a = S/T, b = K/H/R) that mimicked the sequence HKYSWK, which corresponded to amino acid residues 111 to 116 of the nonstructural protein 1 (NS1) of DEN-1. Among the four synthetic peptides corresponding to amino acid residues 110 to 117 of the NS1 of DEN-1, -2, -3, and -4, only one peptide, EHKYSWKS (P14M) of DEN-1, was found to bind to 15F3-1 specifically. Furthermore, P14M was shown to inhibit the binding of phage particles to 15F3-1 in a competitive inhibition assay. Histidine(111) (His(111)) was crucial to the binding of P14M to 15F3-1, since its binding activity dramatically reduced when it changed to leucine(111) (Leu(111)). This epitope-based peptide demonstrated its clinical diagnostic potential when it reacted with a high degree of specificity with serum samples obtained from both DEN-1-infected rabbits and patients. Based on these observations, our DEN-1 epitope-based serologic test could be useful in laboratory viral diagnosis and in understanding the pathogenesis of DEN-1.